Експресія гена протонно-натрієвого обміннику HvNHX2 ячменю в рослинах тютюну покращує показники солестійкості - Ісаєнков, С.В.; Краснопьорова, О.Є.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2015)
Aims. In this study, the gene encoding HvNHX2, a vacuolar Na+/H+ exchanger from barley was transferred to tobacco plants by Agrobacterium-mediated transformation in order to evaluate the improvement of salt tolerance. Methods. Gateaway cloning, RT-PCR and PCR, in vitro plant culture and transformation, physiological tests were combined to evaluate efficiency of transformation and ability to tolerate high salt concentrations. Results. The significant improvement salt tolerance were detected in transgenic tobacco lines after expression of HvNHX2 gene in these plants. The HvNHX2 expressing plants are able to survive on lethal for the wild type concentrations of NaCl (250 mM). Conclusions. Suggested approach to improve the salt tolerance of plants by gene expression one of key Na+/H+ antiporter has a great potential for the further application in plant biotechnology and molecular breeding. Keywords: salt tolerance, tobacco, Na+/H+ exchanger, plant transformation, HvNHX2, plant biotechnology.